Augmented Reality Through the Lens of Eye Tracking. Issue 4 (2nd October 2019) - Josephson, Sheree; Myers, Melina
Abstract : This eye-tracking study compared the usability of Yelp's Augmented Reality application Monocle with its familiar map-based app. Thirty participants (15 in each group) had to find a location in an outdoor mall using one version of the mobile Yelp app while wearing a pair of eye-tracking glasses that recorded the general area of the natural environment or smartphone their eyes focused on. Results showed that AR users could successfully arrive at the destination using the location-based technology that augments a visual display of the physical landscape with digital information. However, Augmented Reality users took longer to find the location than did map users. They also spent more time looking at the mobile smartphone and looked back and forth between the screen and the environment more often than map users. In open-ended questions about preference following the task, 14 of 15 in the AR group said they would likely use the Monocle app in the future to find a location because they could "see exactly" where something was or hated following directions. Since users successfully used this technology and reported enjoying its use, further development of AR for everyday use to complete tasks is encouraged. However, future studies should focus not only on the development of technology but its usability and employ visual communication theories such as Perception Theory (Barry, 2005 ) and Information Processing Theory (i.e., Krause, 1982 ) to help understand users' behavior.